Characterization of the serine acetyltransferase gene family of Vitis vinifera uncovers differences in regulation of OAS synthesis in woody plants - Tavares, Sílvia; Wirtz, Markus; Beier, Marcel Pascal; Bogs, Jochen; Hell, Rüdiger (Frontiers in plant science, 2015)
In higher plants cysteine biosynthesis is catalyzed by O-acetylserine(thiol)lyase (OASTL) and represents the last step of the assimilatory sulfate reduction pathway. It is mainly regulated by provision of O-acetylserine (OAS), the nitrogen/carbon containing backbone for fixation of reduced sulfur. OAS is synthesized by Serine acetyltransferase (SERAT), which reversibly interacts with OASTL in the cysteine synthase complex (CSC). In this study we identify and characterize the SERAT protein family of the crop plant Vitis vinifera. The identified four members of the VvSERAT gene family are assigned to three distinct groups upon their sequence similarities to Arabidopsis SERATs. Expression of fluorescently labelled VvSERAT proteins uncover that the sub-cellular localization of VvSERAT1;1 and VvSERAT3;1 is the cytosol and that VvSERAT2;1 and VvSERAT2;2 localize in addition in plastids and mitochondria, respectively. The purified VvSERATs of group 1 and 2 have higher enzymatic activity than VvSERAT3;1, which display a characteristic C-terminal extension also present in AtSERAT3;1. VvSERAT1;1 and VvSERAT2;2 are evidenced to form the CSC. CSC formation activates VvSERAT2;2, by releasing CSC-associated VvSERAT2;2 from cysteine inhibition. Thus, subcellular distribution of SERAT isoforms and CSC formation in cytosol and mitochondria is conserved between Arabidopsis and grapevine. Surprisingly, VvSERAT2;1 lack the canonical C-terminal tail of plant SERATs, does not form the CSC and is almost insensitive to cysteine inhibition (IC50 = 1.9 mM cysteine). Upon sulfate depletion VvSERAT2;1 is strongly induced at the transcriptional level, while transcription of other VvSERATs is almost unaffected in sulfate deprived grapevine cell suspension cultures. Application of abiotic stresses to soil grown grapevine plants revealed isoform-specific induction of VvSERAT2;1 in leaves upon drought, whereas high light- or temperature- stress hardly trigger VvSERAT2;1 transcription.
Gesehen am 27.01.2017